Analisis Kebiasaan Konsumsi Snack - Fajarullah Bangkit Nugraha; Anggi Rizki; Syamsul Hidayat (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to analyze snack consumption habits among employees of the Department of Transportation of Serang Regency, specifically in the Control and Operational Division. Using a descriptive quantitative method and an online questionnaire distributed to 36 respondents, the research explores snack consumption patterns, timing, stockpiling behavior, purchasing locations, and factors influencing purchase decisions. The findings reveal that most respondents are young to middle-aged and tend to consume snacks in relaxed or social contexts. Minimarkets and local stalls are the main purchasing points, with taste being the most important factor in choosing snacks. Most respondents are also highly open to trying new snack brands. These findings highlight the importance of product and marketing strategies that focus on individual preferences and consumption moments.